Endocrinological and Metabolic Profile in Relation to Pregnancy at the First Insemination in Cows Housed Under Cold Conditions - Cengi̇z, Mehmet; Tohumcu, Vefa; Furqan Asghar Chacher, Muhammad; Hayirli, Armağan; Kaynar, Özgür; İleri̇türk, Mustafa; Yilmaz, Emre; Balli, Bulent; Çolak, Armağan (Ataturk Universitesi, 2022)
This study was performed to investigate the relationship between endocrinological and metabolic profiles and the pregnancy rate at the first insemination in peripartum dairy cows housed under cold conditions. Temperature inside the barn was recorded hourly during the periparturient period. Blood samples were collected before (last 14 day), on the day (0 day), and after parturition (3, 4, 6, 8, 15, 22, and 29 days) from 26 peripartum Simmental cows and analyzed for anti-Müllerian hormone (AMH), β-hydroxybutyric acid (BHBA), insulin-like growth factor 1 (IGF-1), insulin, cortisol, malondialdehyde (MDA), progesterone (P4), thyroid-stimulating hormone (TSH), tri-iodothyronine (T3), and thyroxine (T4) concentrations. The cows were divided into two groups: pregnant (PG) and nonpregnant (NPG) based on results at the first insemination. The average ambient temperature ranged from -7°C to +11°C in the tent barn. Serum AMH (2.00 ± 0.04 vs. 1.89 ± 0.04 mU/l; P<0.006), insulin (2.10 ± 0.03 vs. 2.51 ± 0.05 ng/ml; P<0.0001), MDA (49.0 ± 1.30 vs. 44.0 ± 1.2 ng/ml; P<0.001) and P4 (44.1 ± 2.2 vs. 41.7 ± 2.1 pg/ml; P<0.002) concentrations were different between PG and NPG cows. In conclusion, AMH and insulin have a determinative role on pregnancy rate in peripartum cows housed under cold condition.

Bu çalışma, soğuk koşullarda barındırılan peripartum ineklerde ilk tohumlamada endokrinolojik ve metabolik profil ile gebelik oranları arasındaki ilişkiyi araştırmak amacıyla yapılmıştır. Ortam sıcaklığı, periparturient dönem boyunca saatlik olarak kaydedilmiştir. Anti-Müllerian hormon (AMH), β-hidroksibutirik asit (BHBA), insulin benzeri büyüme faktörü 1 (ILGF-1), insülin, kortizol, malondialdehit (MDA), progesteron (P4), tiroid uyarıcı hormon (TSH), tri-iyodotironin (T3) ve tiroksin (T4) konsantrasyonlarının analizi için 26 adet Simmental inekten doğum öncesi (-14 gün), doğum günü (0 gün) ve doğum sonrası (3, 4, 6, 8, 15, 22 ve 29 gün) farklı aralıklarla kan örnekleri alınmıştır. İnekler, ilk tohumlama sonuçlarına göre geriye dönük olarak gebe (PG) ve gebe olmayan (NPG) olmak üzere iki gruba ayrılmıştır. Çadır ahırda ortalama ortam sıcaklığı -7°C ile +4°C arasında değişmiştir. İneklerin (PG ve NPG) serum AMH (2,00 ± 0,04 vs. 1.89 ± 0.04 mU/l; p<0.006), insulin (2.10 ± 0.03 vs. 2.51 ± 0.05 ng/ml; P<0.0001), MDA (49.0 ± 1.30 vs. 44.0 ± 1.2 ng/ml; P<0.001) ve P4 (44.1 ± 2.2 vs. 41.7 ± 2.1 pg/ml; P<0.002) konsantrasyonları farklıydı. Sonuç olarak, AMH ve insulin soğuk şartlarda barındırılan ineklerde gebelik oranları üzerine belirleyici bir rol oynar.
Keywords: Veterinary Surgery; Veterinary medicine; SF600-1100; Cold stress; cow; fertility; metabolism; pregnancy; Veteriner Cerrahi; 2. Zero hunger; 3. Good health